Asexual male production by ZW recombination in Artemia parthenogenetica. (8th December 2022) - Boyer, Loreleï; Jabbour-Zahab, Roula; Joncour, Pauline; Glémin, Sylvain; Haag, Christoph R; Lenormand, Thomas
Abstract: In some asexual species, parthenogenetic females occasionally produce males, which may strongly affect the evolution and maintenance of asexuality if they cross with related sexuals and transmit genes causing asexuality to their offspring ("contagious parthenogenesis"). How these males arise in the first place has remained enigmatic, especially in species with sex chromosomes. Here, we test the hypothesis that rare, asexually produced males of the crustacean Artemia parthenogenetica are produced by recombination between the Z and W sex chromosomes during non-clonal parthenogenesis, resulting in ZZ males through loss of heterozygosity at the sex determination locus. We used RAD-sequencing to compare asexual mothers with their male and female offspring. Markers on several sex-chromosome scaffolds indeed lost heterozygosity in all male but no female offspring, suggesting that they correspond to the sex-determining region. Other sex-chromosome scaffolds lost heterozygosity in only a part of the male offspring, consistent with recombination occurring at a variable location. Alternative hypotheses for the production of these males (such as partial or total hemizygosity of the Z) could be excluded. Rare males are thus produced because recombination is not entirely suppressed during parthenogenesis in A. parthenogenetica . This finding may contribute to explaining the maintenance of recombination in these asexuals.